Milk production in East African Zebu cattle - Galukande, E.B.; Mahadevan, P.; Black, J.G. (Cambridge University Press, 1962)
Presents estimates of some of the phenotypic and genetic parameters of East African Zebu cattle in West Kenya with respect to milk production. Milk production data at the Baraton, Maseno and Sangalo livestock improvement centres, covering a period of twenty-five to thirty years were analysed. The relationship between milk production and the lenght of lactation, dry period, calving interval, month of calving and age were examined. Lactation length accounted for from 53 to 66 per cent of the total variance in milk yield. Variations in length of dry period caused significant differences in milk yield between, but not within cows. Increasing length of previous calving interval improved current lactation milk yield but month of calving had no significant effect. Yield increased from first to second lactation by 8 percent after which it remained relatively constant up to the fifth lactation. Age at first calving was positively correlated with first lactation milk yield. Intra-herd repeatabilities were 0.55 for milk yield, 0.38 for lactation lenth, 0.17 for calving interval and 0.12 for dry period. The highest estimates of heritability were those obtained for lactation yield and length (0.5); the lowest, for calving interval was close to zero. All heritability estimates had high standard errors. The probable genetic improvement in milk production achieved by the selection practised in the herds was estimated as ranging from zero to 0.15 per cent of the average yield per year.